Exploring the knowledge gap in learning numeracy before formal Schooling. - Ghazali, Munirah (Universiti Sains Malaysia, 2015)

(untitled)
This research investigated Malaysian preschool children's acquisition and understanding of number concepts with respect to number representations. Furthermore this research too explored knowledge regarding parental involvement in facilitation their children's acquisition of numeracy and number concepts. Eleven preschool children were interviewed using Numeracy Task. The Numeracy Task was developed to measure preschool children's knowledge in learning numeracy.